2013
DOI: 10.1161/circulationaha.112.136101
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Statins on Skeletal Muscle Function

Abstract: Background Many clinicians believe that statins cause muscle pain, but this has not been observed in clinical trials and the effect of statins on muscle performance has not been carefully studied. Methods and Results The Effect of STatins On Skeletal Muscle Function and Performance (STOMP) study assessed symptoms and measured creatine kinase (CK), exercise capacity, and muscle strength before and after atorvastatin 80 mg or placebo were administered for 6 months to 420 healthy, statin-naive subjects. No indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
308
3
21

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 439 publications
(347 citation statements)
references
References 25 publications
15
308
3
21
Order By: Relevance
“…16 While short-term studies suggest that statins decrease physical activity in older adults for up to one year, it was unclear if this effect was sustained. 8,9 Our long-term study, that followed men up to an average of 6.9 years, suggests that statins are associated with less physical activity for as long as statins are used. In cross sectional analyses, statin users started with lower physical activity levels compared to nonusers.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…16 While short-term studies suggest that statins decrease physical activity in older adults for up to one year, it was unclear if this effect was sustained. 8,9 Our long-term study, that followed men up to an average of 6.9 years, suggests that statins are associated with less physical activity for as long as statins are used. In cross sectional analyses, statin users started with lower physical activity levels compared to nonusers.…”
Section: Discussionmentioning
confidence: 85%
“…57 If present, these symptoms are most often observed after initiation of statin therapy, and may cause a decline in physical activity. 8 Several short-term studies have suggested that prevalent use or initiation of a statin use is linked to less physical activity in older adults followed for up to a year. 8,9 Other studies have demonstrated that initiation of moderate physical activity increased muscle pain and symptoms in statin users.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been argued that these studies may be biased, as patients who had developed some type of muscle disease in the past were excluded. Supporting this concept, the prevalence of myalgia in observational studies is higher, close to 20% [8,1618]. On the other hand, clinicians have to take into account the nocebo effect, meaning the negative expectations of the patient and their doctors regarding muscular manifestations attributed to statins.…”
Section: Defining Clinical Phenotypesmentioning
confidence: 99%
“…237 Recent systematic reviews 238,246 found no increase in muscle problems in statin groups compared with placebo groups across randomised trials; however, two trials not included in those reviews did find such effects. 247,248 A recent overview commented that there were other possible effects of statins that did not have strong RCT evidence, such as the possible increase of cataracts. 249 An extreme scenario to consider would be to suggest universal treatment at highest tolerated dose, as the associated costs of overtreatment are very small in relation to the costs of undertreatment.…”
Section: Comparison With Previous Literaturementioning
confidence: 99%